STRATEGIC APPROACH TO SUSTAINABILITY-BASED TECHNOPRENEURSHIP: BALANCING THE DYNAMICS OF TECHNOLOGICAL INNOVATION AND SOCIAL RESPONSIBILITY IN THE DIGITAL ENTREPRENEURSHIP ECOSYSTEM - Akmal, Samsul (Technopreneurship and Educational Development Review (TENDER), 2025)
This study aims to examine strategic approaches in sustainability-based technopreneurship, focusing on efforts to balance the dynamics of technological innovation and social responsibility within the digital entrepreneurship ecosystem. Using a qualitative literature review method with descriptive analysis, this research analyzes 25 selected scholarly articles from a total of 50 sources collected via Google Scholar and reputable academic databases spanning the period from 1997 to 2025. The findings reveal that sustainable technopreneurship strategies can be constructed through the integration of values from the Triple Bottom Line, Creating Shared Value, Stakeholder Theory, and Dynamic Capabilities. Case studies from startups such as TaniHub and JALA Tech reinforce the notion that technopreneurial success is not solely dependent on technological superiority, but also on the extent to which they generate positive social and environmental impact. This study concludes that sustainability must be positioned as the core of technopreneurial strategy rather than as a supplementary element. The findings carry significant implications for policy development, entrepreneurship education, and the design of inclusive, socially responsible digital business models.